Implementing an interprofessional point-of-care ultrasound protocol for dyspneic patients in an emergency department as a blended learning concept—Feasibility of Employing Thoracic Ultrasound in Shortness of Breath - Witte, Matthies; Ott, Matthias; Schilling, Tobias; Müller, Martina; Schmid, Stephan; Krohn, Alexander (Frontiers in Medicine, 2023)
Objective: Dyspnea is a common symptom in the Emergency Department, with a wide variety of differential diagnoses. Previous research has demonstrated the diagnostic accuracy of Point-of-CareUltrasound (POCUS) in this field of interest. Our goal was to better establish sonography in our emergency department with a practicable and time effective method. Therefore, we implemented a sonography protocol in an interprofessional emergency team using blended learning as a modern didactic approach and evaluated the learning and teaching success. We named the study FETUS, which stands for "Feasibility of Employing Thoracic Ultrasound in Shortness of Breath". Methods: A demonstration of the POCUS protocol was given, followed by individual supervision during clinical routine. A written manual, a pocket card, and further materials for personal training supplemented the training. A post-training questionnaire measured several parameters regarding the training, e.g., subjective skill-acquisition or media use. Results: 32 medical and nursing staff participated in this study, 14 of whom completed the questionnaire. All training modalities offered were well received. A pre-post comparison of subjective sonographic competence shows a significant increase in both medical and nursing staff. The other items surveyed also indicate the success of the intervention undertaken. Conclusion: The use of different media as a blended learning approach can support the implementation of new measures in the ongoing working routine within an interprofessional team.